О проблеме архаического ритуала в огузском эпосе - Халилов, Агаверди (Народна творчість та етнологія, 2014)
Одним из источников изучения архаического ритуала есть эпос. Многие архаические ритуалы или же их рудименты сохранились в средневековом огузском эпосе «Книга моего деда Коркута». Каждая отдельная часть эпического текста (сказ) связана с определенными ритуалами, в частности с сойлама, бойлама, йум и огузнаме (огузлама), которые коррелируют с социальной структурой огузского общества. The epos is one of the sources that kept the archaic ritual. There are many rituals or their rudiments of the ancient period that belong to the medieval Oghuz epos. The materials of the Oghuz epos (The Book of Dede Korkut, Oghuznameh, and so on) give the possibility to describe these archaic rituals. The fundamental archaic ritual elements are an important source to clear the content, names, and structure of this genre. The ritual archetype component, which is structured in the first part of «The Book of Dede Korkut», is reconstructed in the article. Also in the context of the ritual-folklore relationship, the transformation of ritual into folklore is defined in this article.